Antibiotics and Liver Cirrhosis: What the Physicians Need to Know - Caterina Zoratti; Rita Moretti; Lisa Rebuzzi; Irma Valeria Albergati; Antonietta Di Somma; Giuliana Decorti; Stefano Di Bella; Lory Saveria Crocè; Mauro Giuffrè (MDPI AG, 2021)
The liver is the primary site of drug metabolism, which can be altered by a variety of diseases affecting the liver parenchyma, especially in patients with liver cirrhosis. The use of antibiotics in patients with cirrhosis is usually a matter of concern for physicians, given the lack of practical knowledge for drug choice and eventual dose adjustments in several clinical scenarios. The aim of the current narrative review is to report, as broadly as possible, basic, and practical knowledge that any physician should have when approaching a patient with liver cirrhosis and an ongoing infection to efficiently choose the best antibiotic therapy.